Taxonomia, diversidade e caracterização fisiológica de fungos presentes em solos congelados e termais da Antártica - Hebert Morais Figueredo (2018)
The Antarctic Continent and its islands account for about 14 million km² and harbor different ecosystems with extremes in temperature, low availability of nutrients, water, intense solar radiation, strong winds, among others. In these ecosystems, different microbial groups have adapted and are able to survive; among them, fungi have been outstanding for being able to 5 colonize varied habitats and substrates. Although Antarctica is known for its low annual average temperature, in some regions of the Antarctic Peninsula are found places with high temperatures due to volcanic activity, as in Deception Island. Due to frequent volcanism, Deception Island presents diverse and unique habitats when compared to other regions of Antarctica. In this island fumaroles are found where the waters and the soils can have temperatures between 0 and 100 ºC. 10 Based on these data, this dissertation aimed to characterize the community of fungi present in soil samples from Deception Island in a gradient of 0, 50 and 100 °C. From each sample two procedures were performed to isolate the fungi. In the first procedure all soil samples were processed without a heat treatment. In the second process, the samples underwent different thermal treatments, where the soils obtained at 0 ° C were frozen at -70 ° C for 24 hours; the soils obtained at 50 and 100 °C were heated at 50 and 100 °C for 15 min, respectively. From the isolation procedures, a total of 75 fungal isolates were obtained, of which 32 from the soil that undergoes heat treatment and 43 from the soil that don‘t undergoes heat treatment. Isolates were morphologically grouped and their genomic DNAs obtained for confirmation by microsatellite PCR using the primer (GTG)5. After confirmation, one representative of each obtained molecular 20 group was submitted to the sequencing of different regions of the rDNA and the sequences obtained were compared with sequences of type or reference species deposited in GenBank. In all, 16 distinct taxa were obtained, distributed among the genera Aspergillus, Leohumicola, Mortierella, Penicillium, Pseudogymnoascus and Purpureocillium. Aspergillus was the genus with the highest number of isolates, being obtained from all soil samples at different temperatures, with or without previous heat treatment, followed by Pseudogymnoascus, which was obtained exclusively from the soil sample at 0 °C. The soil samples of Deception Island presented low diversity and species richness, and there were dominance of some taxa. In soil samples at 0 ° C, with and without treatment, Aspergillus sp. 2 showed the highest count, as did Penicillium sp. 1 in the soil sample at 50 ° C and Aspergillus cf. ruber in the soil sample at 100 °C. All isolates were submitted to growth tests at temperatures between 5 and 50 °C for the characterization of mesophilic, psychrophilic/psychotolerant and thermotolerant fungi. Seven isolates of the genus Aspergillus showed thermotolerant behavior at 50 °C. Seventeen isolates of the species Pseudogymnoascus cf. destructans, two of the species Mortierella parvispora and three of the genus Leohumicola were able to grow at a mean temperature of 5 °C, which were selected and subjected to a freezing survival test. All these 23 fungi presented normal growth after exposure to -70 °C for 30 days in the absence of cryoprotectants. From the results obtained we strengthen other results that demonstrate that the fungal community of Deception Island is composed mainly by cosmopolitan organisms, with Aspergillus as the main taxon present. There are also some endemic taxa of Antarctica, represented by the genera Mortierella and Pseudogymnoascus, psychrophylous and psychrotolerant organisms. Among the cosmopolitan taxa, attention is drawn to the presence of potentially pathogenic organisms belonging to the genus Aspergillus, which may pose a risk to humans in the region. Finally, the existence of organisms able of withstanding freezing without the presence of cryoprotectants is a relevant factor, since it suggests that they are capable of producing cryoprotectants from their own cellular machinery and may be sources of metabolites of interest in the future.